math

posted by .

Solve the equation: 6x^2+12x+5=0

  • math -

    In google type:
    quadratic equation online

    When you see list of results click on:
    Free Online Quadratic Equation Solver:Solve by Quadratic Formula

    When page be open in rectangle type:

    6x^2+12x+5=0

    and click option: solve it

    You will see solution step-by step

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    find the slope and y-intercept of the graph of the equation. explain each step and how you got it. 12x + 4y= 24 -first you move the 12x to the other side of the equation to isolate the 4y -Divide the whole equation by 4 to give a single …
  2. calc

    What is dy/dx of y=12/12X-y^3 ???? Any idea anyone?
  3. algebra2

    1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2 Check …
  4. help...solving a polynomial....algebra

    solve this please....help me....12x(squared)+7x-10 Do you wish to factor this trinomial?
  5. Math

    Consider the equation x^2 + 20 = 12x A) draw geometric diagram representing this equation. B) Show how to complete the square geometrically. C) Solve the equation.
  6. Math

    solve for the conic in the equation y^2-6y+12x+33=0
  7. Algebra

    To solve 9x^2-12x+4=49 by using the Square Root Property, you would first rewrite the equation was as A. 9x^2-12x-45=0 B.(3x-2)^2=+/-49 C.(3x-2)^2=7 D.(3x^2)^2=49
  8. Calculus!! HELP!!

    1) The sides of the triangle shown increase in such a way that (dz/dt=1) and (dx/dt=(3dy/dx)) At the instant when x = 12 and y = 5, what is the value of dx/dt?
  9. math

    Solve the system:4x+2y-13=0 and 3x=5y+26 by elimination. 3 (4x+2y-13=0) 12x+6y-26=0 4 (3x=5y+26) 12x=20y+104 I need to subtract since the signs are the same: 12x+6y-26=0 Since they don't match up, I'm having trouble subtracting them. …
  10. Algebra

    What is the vertex form of the equation? y = -x^2+12x-4 My work: -(x^2 + 12x)-4 -(x^2 + 12x + 36)-4 + 36 Y= -(x+36)^2 + 32 Is this correct?

More Similar Questions